Analysis of Classroom Infrastructure Facilities on Student Motivation at SMK Negeri 2 Karanganyar - Purwaningsih, Lisa; Agus Efendi; Sulistiyo, Budi (Journal of Global Hospitality and Tourism Technology, 2025)
Learning motivation is a person's psychological condition that encourages learning activities. Students' learning motivation can be influenced by several factors, including the condition of the infrastructure available in schools and classrooms.  The purpose of this study was to see the condition of infrastructure facilities whether there is an influence on student learning motivation in class XI RPL at SMK Negeri 2 Karanganyar. The research method uses quantitative methods by collecting interview and questionnaire data with a sample of 30 students in class XI RPL. The results of the study show the influence of infrastructure on learning motivation as evidenced by the results of the correlation test rcount> rtable value, namely 0.748> 0.361 with a significance level of 5% in the range of 0.60 - 0.79 which is categorized as “strong”. Each instrument is tested for reliability which results in a value of 0.80> 0.361 which means reliable. While the percentage of each instrument gets 75.1% for infrastructure facilities and 74.9% for motivation. In other words, school infrastructure facilities have an effect on the motivation of class XI students in learning activities.